2013
DOI: 10.1111/gcbb.12124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of harvest frequency and biosolids application on switchgrass yield, feedstock quality, and theoretical ethanol yield

Abstract: Sustainable development of a bioenergy industry will require low-cost, high-yielding biomass feedstock of desirable quality. Switchgrass (Panicum virgatum L.) is one of the primary feedstock candidates in North America, but the potential to grow this biomass crop using fertility from biosolids has not been fully explored. The objective of this study was to examine the effects of harvest frequency and biosolids application on switchgrass in Virginia, USA. 'Cave-in-Rock' switchgrass from well-established plots w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…In addition, optimal quality varies depending on the conversion technique used to generate energy (Liu et al, 2015). Generally, we found no significant differences in the concentrations of fiber constituents among N rates within each sampling date (Table 1) (Table 1).…”
Section: Biomass Quality Of Standing Switchgrassmentioning
confidence: 81%
“…In addition, optimal quality varies depending on the conversion technique used to generate energy (Liu et al, 2015). Generally, we found no significant differences in the concentrations of fiber constituents among N rates within each sampling date (Table 1) (Table 1).…”
Section: Biomass Quality Of Standing Switchgrassmentioning
confidence: 81%
“…A significant body of literature has demonstrated numerous agronomic benefits associated with land application of biosolids to pastures (Adjei & Rechcigl, 2002; Barbarick, Doxtader, Redente, & Brobst, 2004; Sigua et al., 2005). Land application of biosolids to perennial pasture provides essential plant nutrients and organic matter and serve as a liming agent to acid pasture soils (Adjei & Rechcigl, 2002; Antille et al., 2017; Avery et al., 2018; Liu, Fike, Galbraith, & Fike, 2015a, 2015b; Sigua et al., 2005; Tiffany et al., 2001a, 2001b). Research demonstrated that when applied at equivalent N rates, biosolids resulted in either similar or greater forage production as inorganic fertilizer (Adjei & Rechcigl, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these mixed species plantings provide resources important for breeding birds including potential nest sites and arthropods for nestling sustenance (Simpson, 1949;MacArthur and MacArthur, 1961;Wiens, 1974;Rotenberry, 1985;McCoy et al, 2001). Biofuel production also requires annual or semi-annual harvests, with a main cutting traditionally during fall or winter months to maximize total biomass, and a potential secondary cutting for forage or biomass during the summer (Vogel et al, 2002;Fike et al, 2006;Liu et al, 2015). As such, the timing of these additional harvest events can be detrimental to avian species if they occur during the breeding season (Roth et al, 2005) because they destroy active nests, remove vegetative cover, and reduce food availability (Bollinger et al, 1990;Kershner and Bollinger, 1996;Warren and Anderson, 2005;Perlut et al, 2006).…”
Section: Introductionmentioning
confidence: 99%